Apoptotic sperm biomarkers and the correlation between conventional sperm parameters and clinical characteristics. (10th May 2017) - Hichri, R.; Amor, H.; Khammari, M.; Harzallah, M.; El Fekih, S.; Saad, A.; Ajina, M.; Ben Ali, H.
Summary: The principal aim of this retrospective study was to examine the relationship between sperm apoptotic biomarkers and the patient's biclinical characteristics, the conventional sperm parameters and the results of assisted reproductive technology. Sperm analysis, activated caspases, annexin V staining for phosphatidylserine (PS) externalisation and labelling assay for DNA fragmentation were assessed in 122 males of infertile couples. Fifty‐seven couples were allocated to the natural conception group, and 65 couples underwent IVF or ICSI. Semen of IVF/ICSI patients showed a higher proportion of apoptotic spermatozoa in their spermatozoa when compared with a natural conception group ( p  < .05). Sperm apoptotic biomarkers correlated with age, FSH, and conventional sperm parameters. DNA fragmentation correlated positively with the percentage of semen having externalised PS ( r  = .78, p  = 0) and activated caspases ( r  = .71, p  = 0). Patients without clinical pregnancy had higher frequency of DNA fragmentation, externalised PS and activated caspases compared to patients with clinical pregnancy ( p  < .001). The best specificity and greater sensitivity were obtained with the test of the DNA fragmentation compared to the other biomarkers. Among the apoptotic biomarkers, only DNA fragmentation was found to predict natural or assisted pregnancy better than conventional sperm parameters.